Educação em direitos humanos para o combate ao sexismo : contribuições do letramento na disciplina de Língua Portuguesa - Oliveira, Cristiane Fontes de (Universidade Federal de São Carlos, 2009)
The achievements of women's social movements have granted such group historically denied rights, it is however noted nowadays that socially constructed values reproduce sexist concepts with regards to human relationships and it is likewise remarkable the important role school education has to encourage attitudes against sexism. On such matter and in the Portuguese language teaching environment of a state school, the purpose of this research is analysing students' concepts on the condition of women in contemporary, with the scope to trigger reasonings on the way such school discipline can contribute to debates on sexism through a methodological approach which can enable the development of writing and reading skills as well as the development of the student's critical reflections about human relationships. From this point and through Cultural Circles on the basis of Paulo Freire's theoretical perspective, students from a state school analysed literary and informational texts about the condition of women, aiming to understand the importance of the referred activity for the setting up of feminist ideas. The survey is characterised as exploratory and brought up hypotheses with regards to the Methodology of the Portuguese Language Teaching and Human Rights Education, specifically against sexism.
Keywords: Educação - consciência crítica; Educação em Direitos Humanos; Sexismo; Letramento; Freire, Paulo Reglus Neves, 1921-1997; Língua portuguesa - estudo e ensino; CIENCIAS HUMANAS::EDUCACAO